HUBUNGAN FAKTOR INTERNAL PACAR DENGAN KEKERASAN DALAM PACARAN - Ivanna Manoppo (Fakultas Keperawatan, Universitas Klabat, 2021)
Many women are victims of violence by their boyfriends. The act of violence can be in the form of being overly coercive and controlling their partner. This is due to the influence of consuming alcohol. The age of Boyfriend is also associated with premature sexual violence and unwanted sexual activity in adolescents. The purpose of this study was to determine the relationship between factors internal of boyfriends and violence in dating. The research method was observational analytic with cross sectional approach. The sampling technique was used purposive, with a sample of 99 respondents. The result of the study showed that include :. There is no relationship between internal factors of boyfriends when viewed from age with a value of p = 0.145 <0.05.There is a very significant positive relationship with factor internal of boyfriend when viewed from the use of alcohol with a value of p = 0.00 and a moderate correlation value. Recommendations for future research can be examined on a larger population and sample to obtain the accuracy of data, and can examine other factors such as the length of dating relationships with the incidence of dating violence.